Effects of Dietary Protein Levels on the Growth Performance and Carcass Characteristics of Nakorn Thai Black-boned Chickens - Norakamol Laorodphan, Punnares Rattanapradit, Khongdet Phasinam, Rangsun Charoensuk, Tossaporn Incharoen, Prasit Yimket, Chirawath Phatsara (Forest Chemicals Review, 2022)
Introduction: Customers are increasingly demanding to consume black bone chicken. They believe that black bone chicken is good for health because it is rich in amino acids of Carnosine. But the production of black bone chicken is still not as developed as it should be. There is still a lack of information on the nutritional requirements that will help the production of black bone chicken more efficiently. Purpose: To evaluate growth performance and carcass characteristics of Nakorn Thai black bone chicken fed by different levels of protein. Materials and Method: Ninety-six 14 days old Nakorn Thai black-bone chickens of an average initial body weight 32.87+0.77 g were used. Chickens were divided into 4 groups as the follow regressive protein levels; group 1 fed 20, 19, 18 and 17%CP (T1), group 2 fed 19, 18, 17 and 16%CP (T2), group 3 fed 18, 17, 16 and 15%CP (T3) and group 4 fed 17, 16, 15 and 14%CP (T4) during 0-2, 2-6, 6-10 and 10-16 weeks of age, respectively. Results: ADG and FCR had no significance among treatments during 0-2, 2-6 and 10-16 weeks of age (p>0.05), while body weight of T1 tended to be higher than T4 during 6-10 weeks of age (p=0.07). Moreover, weight gain and ADG of T1 were clearly higher than T4 (p<0.05). Furthermore, the carcass percentage of T1 had a tendency to be higher than T4 (p=0.11). Breast percentage of T1 and T2 were significantly higher than T4 (p<0.05) and thigh percentage of T1 was significantly higher than T3 and T4 (p<0.05). Conclusion: dietary crude protein contents of 20, 19, 18 and 17% during 0-2, 2-6, 6-10 and 10-16 weeks of age had higher growth performance and carcass characteristics compared with other crude protein levels.